Effects of empty fruit bunch biochar split application on yield and soil organic dynamics in Amaranthus viridis L. and corn cultivation - Tan, Wei Loon (2017)
Biochar soil amendment has been widely reported to improve crop performance and soil properties. While most studies reported on a single application at the start of the cropping, there are interesting question on whether there is any beneficial effects to the crop and soil if the biochar is applied in lower doses but with higher frequency. Therefore, this study was carried out (i) to determine the physical and chemical characteristics of oil palm empty fruit bunch (EFB) biochar and its nutrient retention properties (ii) to evaluate the effects of single and repeated EFB biochar application on crop performance and soil chemical characteristics in three crop cycles of Amaranthus viridis and bioavailability of nutrients in soil after 24 months of fallow period. (iii) to assess changes in soil carbon and EFB biochar morphology and composition changes 34 months after application. The EFB biochar was collected and characterized for its physical and chemical characteristics. A laboratory leaching study with three types of soil and field container study with different EFB biochar application rates (0, 10, 20, 30 t/ha EFB) was conducted to determine the effect of EFB biochar on nutrient retention and crop nutrient uptake. A field trial was carried out to determine the effects of single and repeated EFB biochar application (B0, B10, B10+10, B10+10+10, B30) on crop performance and soil chemical properties in three crop cycles of A. viridis. The EFB biochar and soil samples were also collected 34 months after intitial application to observe the changes in biochar morphology and surface functional groups, and soil total C and dissolved organic C (DOC). The characterization of EFB biochar showed it has the potential to be a good soil amendment (pH 8.6, CEC 59.9 cmol(+)/kg, 43.7 % C, high exchangeable bases content, 17.07 m2/g surface area, high internal surface area). The field trial with EFB biochar soil amendment showed significant increase in A. viridis economic fresh yield and dry matter weight. However, the yield response of A. viridis towards EFB biochar was responsive to 10 t/ha EFB biochar, with no increment with higher biochar application rate. The EFB soil amendment increased soil exchangeable bases; with mixed effects detected for soil pH, C, N and CEC. The field container experiment showed that EFB biochar reduced nitrate and ammonium leaching while contributing towards potassium leaching. The better nutrient retention in soil led to higher nutrient uptake in A. viridis. The nutrient bioavailability assay showed treatment B10+10 having significant higher dry matter weight and nutrient uptake. The single and repeated EFB biochar application showed mixed results, with the single high dose of EFB biochar treatment showing sustained improvement in soil properties (pH, exchangeable bases) while the repeated low doses of EFB biochar giving significant higher plant nutrient uptake. Soil TC and DOC did not response to the EFB biochar application. The scanning electron microscope (SEM) image of EFB biochar samples collected after 34 months showed the surface interaction with soil particle while the fibre structure remains intact. The Fourier transform infrared spectroscopy (FTIR) spectra revealed changes in biochar surface functional groups, increase in aromatic C=C and aliphatic C-H and reduction of alcohol OH. In conclusion, EFB biochar was found to be a potential soil amendment for short term, leafy vegetable crop. Further studies are needed, especially on the long term continuous leafy vegetable cropping system.